2017
DOI: 10.3855/jidc.8223
|View full text |Cite
|
Sign up to set email alerts
|

Giardia duodenalis genotypes among schoolchildren and their families and pets in urban and rural areas of Sinaloa, Mexico

Abstract: Introduction: Giardiasis is a human health concern worldwide, especially among schoolchildren. Giardia duodenalis genotypes A and B are infective to humans, but their zoonotic potential remains controversial. In Mexico, the most prevalent genotype is A, but B was also detected in southeastern Mexico. In Sinaloa state, northwestern Mexico, giardiasis is highly prevalent, but Giardia genotypes have been poorly studied. Methodology: This study aimed to investigate the distribution and clinical-epidemiological cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
(65 reference statements)
3
13
0
1
Order By: Relevance
“…In the present study, assemblage A sequences were more prevalent than assemblage G sequences, and no mixed assemblage A and G infections were detected. This result is consistent with data from previous studies in pets in China and Mexico [ 24 , 28 ]. Thus far, assemblages A-C, E and G have been identified in rodents worldwide, and nearly all tested samples contained at least either assemblage A or B [ 12 , 13 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, assemblage A sequences were more prevalent than assemblage G sequences, and no mixed assemblage A and G infections were detected. This result is consistent with data from previous studies in pets in China and Mexico [ 24 , 28 ]. Thus far, assemblages A-C, E and G have been identified in rodents worldwide, and nearly all tested samples contained at least either assemblage A or B [ 12 , 13 ].…”
Section: Resultssupporting
confidence: 94%
“…Sub-assemblage AII has also been identified in humans in China. Cross-species transmission of G. duodenalis assemblage AI in Mexico and in Brazil has been recently reported [ 28 , 29 ]. This finding suggests that chipmunks infected with assemblage AI were probably the source of human giardiasis due to frequent contact of the two species in that specific area.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, due to the high prevalence of Giardia among children, and its higher exposure to dogs in poor seting, it is believed that Giardia has developed zoonotic transmission. This possibility has been reported concordantly by genotyping and molecular studies from Mexico [40], Jamaica [41], and Cambodia [42].…”
Section: Incidence and Burden Of Diseasesupporting
confidence: 60%
“…Other studies have also shown that the prevalence of G . intestinalis was associated with infection of children and foals [ 24 , 28 ]. The difference between the prevalence of G .…”
Section: Discussionmentioning
confidence: 99%